Epidemiological profile of newborns diagnosed with COVID-19 in a private maternit hospital in the Northeast between january 2020 and december 2021 (Research, Society and Development, 2023)
Objective: To evaluate the epidemiological profile of newborns (NB) diagnosed with COVID-19 by RT-PCR between January 2020 and December 2021, to obtain information on symptoms and risk factors associated with infection and patient prognosis. Methods: This is an observational, analytical, and descriptive cross-sectional study that investigated the epidemiological profile of 17 newborns (NB) diagnosed with COVID-19 by reviewing medical records. Results: The majority of the newborns under consideration were born full-term, with a median gestacional age of 38 weeks, to mothers without any previous comorbidities or complications during pregnancy. The primary indicators for a potential COVID-19 infection included fever at 52.9%, respiratory distress at 35.2%, diarrhoea at 11.7%, and contact with persons suspected of being infected at 11.7%. The disease's progression was relatively mild, with asymptomatic NB representing 29.4% of the sample and symptomatic NB presenting with non-severe symptoms such as abdominal distension (17.6%), bloody stools (11.7%) and tachycardia (35.9%). The study found that hospital discharge occurred in 88.2% of newborns, while death was observed in 11.7% of the sample. Notably, one death (5.88%) was attributed directly to COVID-19 infection. Conclusion: The epidemiologic results found in our study were similar to the vast majority of published studies on this topic, including reports and case series. However, there is still a need for more studies with larger sample sizes.